2012
DOI: 10.1177/2047487312449308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of patient education in the management of coronary heart disease: a systematic review and meta-analysis of randomized controlled trials

Abstract: Our review had insufficient power to exclude clinically important effects of education on mortality and morbidity. Nevertheless it supports the practice of CHD secondary prevention and rehabilitation programmes including education as an intervention. Further research is needed to determine the most effective and cost-effective format, duration, timing, and methods of education delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
2
23
0
6
Order By: Relevance
“…In patients with coronary heart diseases, evidence (though inconclusive) suggested that education may improve health-related quality of life and reduce overall health care costs. 19 Similar findings were reported in another review of the Heart Manual as a self-help home-based cardiac rehabilitation intervention. 26 Rehabilitation of older people…”
Section: Cardiac Rehabilitationsupporting
confidence: 70%
“…In patients with coronary heart diseases, evidence (though inconclusive) suggested that education may improve health-related quality of life and reduce overall health care costs. 19 Similar findings were reported in another review of the Heart Manual as a self-help home-based cardiac rehabilitation intervention. 26 Rehabilitation of older people…”
Section: Cardiac Rehabilitationsupporting
confidence: 70%
“…A recent systematic review and meta‐analysis reported that patient education has little effect on the mortality and morbidity of patients with CHD (Brown et al . ). The same review, however, found education did improve health‐related quality of life and reduce health care use.…”
Section: Discussionmentioning
confidence: 97%
“…Participants in our study found it was important to rectify existing knowledge gaps about cardiac disease to understand its cause, treatment and to enhance their selfcare capabilities. A recent systematic review and metaanalysis reported that patient education has little effect on the mortality and morbidity of patients with CHD (Brown et al 2013). The same review, however, found education did improve health-related quality of life and reduce health care use.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although we recruited patients from an outpatient clinic who did not intend to participate in the phase 2 hospital-based cardiac rehabilitation program, the patients might have attended an inpatient rehabilitation, which comprised diet counselling, cardiac rehab exercises, and patient education. These components are similar to the interventions that are known to be effective in improving patient outcomes (Brown, Clark, Dalal, Welch, & Taylor, 2013). As a result, the usual care received during the inpatient phase may mask the study intervention effect.…”
Section: Discussionmentioning
confidence: 99%